Productivity of binary crops under the application of different cultivation technology elements - M. Pavlenko; V. Kovalenko; O. Pikovska; O. Tonkha (Рослинництво та ґрунтознавство, 2025)
Enhancing cultivation technologies adapted to climate change while maintaining soil fertility is a key objective in the agricultural sector. Particular attention is given to implementing intercropping systems and selecting the most effective technological elements to maximise agroecosystem productivity. This study aimed to examine the effects of various biopreparations on the productivity of a barley-pea binary crop and the mineral nitrogen content in the soil. The research was conducted in 2023-2024 at the experimental field of the Separate Subdivision of the National University of Life and Environmental Sciences of Ukraine, “Agronomic Research Station” in the Kyiv Region. The experiment comprised five treatments: control, biochar, humus extract, EM-5 preparation, and LF 20 humate. Plant samples for biomass assessment were collected on the 30th, 60th, and 90th days after emergence. Soil samples from the 0-10 cm, 10-20 cm, and 20-30 cm layers of typical medium loam chernozem were analysed for mineral (nitrate and ammonium) nitrogen content following DSTU 4729:2007. It was established that the best seedling emergence in the pea-barley intercropping system was observed with the application of biochar, reaching 64 and 140 plants per m2, respectively. However, by the 30th day, biochar application suppressed plant growth, whereas the highest values were recorded in the humus extract treatment, followed by the EM-5 treatment. A similar trend was observed on the 60th day after emergence. Pea yield in the LF 20 humate treatment was 1.56 t/ha, while in the humus extract treatment, it was 1.52 t/ha. The corresponding barley yields were 4.52 t/ha and 5.19 t/ha. Biochar application was the least effective in enhancing crop productivity in intercropping; the pea yield increase relative to the control was negligible, while barley yield decreased by 0.23 t/ha. This decline was attributed to the deterioration of the soil nitrogen regime, as mineral nitrogen content in this treatment was the lowest on the 60th day after crop emergence, ranging from 31.1 to 34.8 mg/100 g of soil. The findings hold practical significance for improving organic fertilisation systems in binary cropping and enhancing agroecosystem resilience. They may be utilised by agricultural producers across various ownership structures